Ironi Perdagangan Manusia Berkedok Pengiriman "Pahlawan Devisa Negara" - Kusumawati, Mustika Prabaningrum (Jurnal Hukum Novelty, 2017)
Human trafficking disguised as shipping heroes of countrieâs foreign exchange occured because the government does not exercise its function properly. The existence of Indonesiaâs Criminal Law Book (KUHP), The Act of 39 Year 2004 About Placement and Protection of Indonesian Labor, The Act of 21 Year 2007 About Eradication of Human Trafficking, as well as several other laws are expected to be optimally applied. In connection with the shipment of labors that disguise as heroes of countrieâs foreign exchange, it is urgent to prevent it comprehensively and integrally which covers: direct prevention, indirect prevention, prevention with some environment restoration, and prevention through the attitude upgrading.